Alice the tennis fairy - Meadows, Daisy (New York : Scholastic Inc., 2010)
While everyone in Fairyland is getting ready for the Fairy Olympics, Jack Frost's goblins steal the Sports Fairies' magic objects, and Rachel and Kristy must snag Alice's magic racquet, the goblins are going to win --- game, set, and match!
Originally published with series title The sporty fairies: London : Orchard Books, 2008
2
006-009
Keywords: Walker, Rachel (Fictitious character) -- Juvenile fiction; Tate, Kirsty (Fictitious character) -- Juvenile fiction; Fairies -- Juvenile fiction; Olympics -- Juvenile fiction; Magic -- Juvenile fiction; Jack Frost (Legendary character) -- Juvenile fiction; Goblins -- Juvenile fiction; Fantasy fiction -- Juvenile fiction; Tennis stories -- Juvenile fiction; Sports stories -- Juvenile fiction; Walker, Rachel (Fictitious character) -- Fiction; Tate, Kirsty (Fictitious character) -- Fiction; Fairies -- Fiction; Olympics -- Fiction; Magic -- Fiction; Jack Frost -- Fiction; Goblins -- Fiction; Sports -- Fiction; Tennis stories